(untitled) (Educational Dimension, 2023)
This study aims to determine the conceptual foundations of a unified personalized open computer-integrated learning environment for the Junior Academy of Sciences of Ukraine (JASU). The research tasks include identifying priority directions for developing students’ research competence, analyzing the innovative activities of JASU in implementing cloud-based ICT (Information and Communication Technology), and defining the objectives and structure of the "Learning Interaction Support Server" software complex as the basis for a unified personalized open computer-integrated learning environment for JASU. The research object focuses on the process of developing students’ research competence within JASU, while the subject encompasses the concept of a unified personalized open computer-integrated learning environment for JASU based on network ICT services. Research methods employed in this study involve analyzing regulatory documents, scientific publications, articles, monographs, conference proceedings, and seminars. Additionally, an analysis of the extracurricular education system and the structure and activities of JASU was conducted. The research findings entail identifying priority directions for fostering innovative thinking and culture, designing an acmeological educational space considering the innovative development of education, personal demands, societal and state needs. Furthermore, the innovative activities of JASU were examined, and models for developing students’ research competence within JASU were proposed. The implementation of cloud technologies, as the most promising innovative direction for the development of network ICT services, was discussed. Moreover, the tasks and structure of the "Learning Interaction Support Server" software complex—an adaptive distributed information and knowledge management system and personalized networked virtual electronic platforms for educational actors—were determined. The main conclusions and recommendations highlight that the creation of a unified personalized open computer-integrated learning environment for JASU will ensure the presence of all educational process participants, regardless of time and location. It will also promote the development and effective utilization of managed educational information resources, including personalized databases for students and educators. Ultimately, the motivation and productivity of scientific research will be significantly enhanced.